Perkawinan Campuran Dalam Dampak Globalisasi Pada Hukum Keluarga - Pahutar, Agus Anwar; Ritonga, Mahyudin; Hanafi, Abdul Halim; Siregar, Neila Hifzhi (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
Globalization has an impact on various aspects of human life, without exception in the case of marriage, where in this era of globalization mixed marriages have become commonplace. This article therefore explores how different countries deal with the legal issues arising from marriages between citizens of different jurisdictions. The study focuses on analyzing legal regulations and practices related to legal status, citizenship, and child custody in the context of mixed marriages. Through qualitative research that includes a literature review and case analysis, this article discusses the implications of the different regulations in different countries and their impact on the individuals and families involved. From the analysis, it is found that: First, Differences in international family law. Mixed marriages often raise complex legal issues, including differences in marriage, divorce, child custody and inheritance laws, which can vary significantly between countries Second, Citizenship and its legal implications. Citizenship factors have important implications in mixed marriages, affecting everything from legal rights and obligations in different countries, to issues such as child custody and access to social services. Third, social integration challenges. Families in mixed marriages may face challenges of social integration and cultural adaptation, which require sensitive and inclusive approaches from society and government agencies.